Methods to determine the risk of unintended allergen presence related to the dispersion of allergenic food particles in food production areas. (June 2021) - Meima, Marie Y.; Remington, Benjamin C.; Blom, W. Marty; Baumert, Joseph L.; Taylor, Steven L.; Jeffery, Brett; Robert, Marie-Claude; Houben, Geert F.; Lucas Luijckx, Niels B.
Abstract: Allergenic food particles (typically ~0.5–5 mm) may unintentionally end up in food products during production and can pose a risk for the allergic consumer. A single particle can provoke allergic symptoms in an allergic consumer when the dose of allergenic protein exceeds minimal eliciting doses. However, there is a lack of fundamental knowledge and research regarding allergenic particle behavior in food production and the resulting probability of their unintended presence in food products. In this study, the behavior of various types of particles encompassing a range of sizes and shapes (i.e. mustard seeds, sesame seeds, hazelnut pieces, walnut pieces and decoration pearls) was observed under controlled laboratory conditions and in a food production test facility. The main behavioral endpoints studied were rebound height and distance from and distribution around the rebound point. We found that the most determining particle characteristic for behavior was particle shape (spherical vs. non-spherical). In the laboratory, spherical mustard seeds showed an average rebound height of at least 3-fold higher than the non-spherical shaped sesame seeds, walnut pieces and hazelnut pieces. The distance from the rebound point after dropping was also considerably larger for mustard seeds, i.e. regularly up to 150 cm, while the majority of sesame seeds, walnut pieces and hazelnut pieces showed a distance from the rebound point of up to 30 cm, 7 cm and 4 cm, respectively. Experimental results from the test facility were in line with the results of the experiments in the laboratory, and provided additional insights in particle behavior for specific factory characteristics such as a moving belt. The experiments led to a concept for the definition of risk zones around a particle application and handling point, and can ultimately support efficient design of a production line and area and the application of tailored risk management measures with the goal to limit allergenic particle cross contamination. Highlights: Allergenic particle behavior was studied under controlled conditions. Particle characteristics influence particle behavior to large extent. A risk zone can be defined by observing particle behavior during production. Tailor-made prevention and cleaning measures can be applied at a risk zone.